2016
DOI: 10.1007/s11420-016-9520-x
|View full text |Cite
|
Sign up to set email alerts
|

Rating a Sports Medicine Surgeon’s “Quality” in the Modern Era: an Analysis of Popular Physician Online Rating Websites

Abstract: There was a low degree of correlation among online websites for surgeon ratings. Female surgeons and those with fewer years in practice appear to have higher ratings on these websites; comment content analysis suggests that high and low ratings are influenced by perceived surgeon competence and affability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
49
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 18 publications
6
49
3
Order By: Relevance
“…The online presence of orthopedic surgeons has grown substantially, and most surgeons have been rated by their patients on at least one independent website. 17,19,21 Although most overall rat-ings and comments are positive, the number of ratings across all of these websites is low, consistent with the current findings. 17,19,21 Despite the variable quality of these ratings, patient awareness of these websites has grown during the past decade.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The online presence of orthopedic surgeons has grown substantially, and most surgeons have been rated by their patients on at least one independent website. 17,19,21 Although most overall rat-ings and comments are positive, the number of ratings across all of these websites is low, consistent with the current findings. 17,19,21 Despite the variable quality of these ratings, patient awareness of these websites has grown during the past decade.…”
Section: Discussionsupporting
confidence: 86%
“…17,19,21 Although most overall rat-ings and comments are positive, the number of ratings across all of these websites is low, consistent with the current findings. 17,19,21 Despite the variable quality of these ratings, patient awareness of these websites has grown during the past decade. [14][15][16] A survey of US patients found that 65% were aware of physician ratings, 35% of those patients had chosen a physician based on good ratings, and 37% had avoided a physician because of negative ratings.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The trends observed in our study have also been identified in other medical specialties. In a study of 275 sports medicine surgeons, Nwachukwu et al (19) found surgeon competence and communication to be the main topics for comment inclusion. Additionally, in a large retrospective analysis of Yelp reviews on emergency medicine physicians, communications with doctors and nurses were primary reasons underlying patients leaving comments on online platforms (20).…”
Section: Discussionmentioning
confidence: 99%
“…Polled physicians are concerned about the usefulness of Web-based ratings and how they could negatively impact their practice [ 18 ]. Comparing websites scores of individual sports medicine doctors revealed a low degree of correlation between websites raising concerns about their reliability [ 19 ]. When reviews were correlated with scores, very high and very low ratings were correlated with the patient’s perception of physician skill and quality, which would seem difficult for patients to truly know [ 20 ].…”
Section: Discussionmentioning
confidence: 99%